P129 Intestinal ultrasound at week 12 predicts long-term endoscopic response to biologics in ulcerative colitis. (30th January 2023) - Allocca, M; Dell'Avalle, C; Furfaro, F; Zilli, A; Radice, S; D'Amico, F; Peyrin-Biroulet, L; Fiorino, G; Danese, S
Abstract: Background: Intestinal ultrasound (IUS) is accurate to assess endoscopic activity in ulcerative colitis (UC). The Milan ultrasound criteria (MUC) is a validated scoring system to assess and grade endoscopic activity in UC. The most accurate cutoff value for MUC was > 6.2 for endoscopic activity (defined as a Mayo endoscopic score, MES ≥ 2). The aim of this study was to assess the predictive value of IUS and MUC for treatment response in a longitudinal cohort, using colonoscopy (CS) as reference standard. Methods: Consecutive active UC patients starting biologic therapy were included. All patients underwent CS, IUS, clinical and faecal calprotectin (FC) evaluations prior commencing a biological therapy, and within one year (mean 9.4 months). In addition, patients were evaluated by IUS, clinical and FC assessments at week 12. The primary objective was to evaluate whether ultrasound improvement (defined as MUC ≤ 6.2) at week 12 predicted endoscopic improvement at reassessment (defined as MES ≤ 1). Endoscopic remission was defined as MES = 0. Results: Forty-nine patients were included (59% under infliximab, 29% under vedolizumab, 8% under adalimumab, 4% under ustekinumab). MUC and MES correlated at reassessment (r= 0.767, p < 0.001). Ultrasound improvement at week 12 was the only independent predictor for MES ≤ 1 and MES = 0 at reassessment (OR 5.80, p = 0.010; OR 10.41, p = 0.041; respectively). Ultrasound improvement at week 12 showed NPV of 96% for detecting MES = 0. A ≥ 2 reduction of the MUC score predicted MES=0 (area under the curve, AUC 0.816). MUC ≤ 4.3 was the most accurate cut-off value for MES = 0 (AUC 0.876). The responsiveness ratio of Guyatt for the MUC was 1.73 and the standardized effect size ratio was 1.6. Both these values > 0.8 indicate a large effect of responsiveness for the MUC. Conclusion: MUC is highly accurate to monitor treatment response. Ultrasound improvement after the induction period may predict long-term endoscopic response. The MUC may be used both in clinical trials and routine practice.